Full Stack Development - Software Development for The Full Development Stack Using the Example of a Lesson Planning System - Tomasz SKŁADANEK; Bartosz CHECHŁACZ; Paweł KACZMAREK; Zbigniew PIOTROWSKI (Communications of International Proceedings, 2022)
In this paper, the authors describe the process of software development, an example of which is a system for planning teaching activities. It describes how the ICT system was programmed, starting with the database, service layer and facades, followed by the creation and deployment of REST APIs and the integration with these interfaces on the Graphical User Panel side using an HTTP client. The overall described solution enables further research into the rapid and error-free design of ICT systems for capturing, processing and displaying research and its results.
Keywords: Fullstack; backend; frontend; database; GUI; JWT; Spring Boot; REST API; Docker; MinIO; PostgreSQL